O consumo radiofônico no ecossistema midiático atual : as práticas cotidianas de ouvintes gaúchos residentes nos ambientes rural e urbano - Avrella, Bárbara (2021)
In this thesis we aim to understand the presence of radio media in the daily practices of subjects who live in rural areas and in urban areas of Rio Grande do Sul, analyzing the blurred borders between these places from the information and communication technologies. For this, we conducted a qualitative research with 18 people, nine living in rural communities in the county of Tuparendi and nine residents of a vertical condominium in Porto Alegre. We seek to identify the listeners' habits related to radio media; to verify how everyday relationships and activities influence the appropriation of the environment on a daily basis; to understand how this habits change the listeners’ life trajectory. In addition, we try to detect how the differents media content has affected the relationship between radio media and its listeners. Then, we developed a theoretical research based on aspects relates to daily life, media consumption, Media Ecology and digital Technologies, transformations in the radio media and the audience, as well as issues linked to the urban and rural context in these two locations. For the study, we use the triangulation proposed by Flick (2009), using as a collection method the semi-standardized interview, documentation, audio recording and interpretation, qualitative content analysis. As a conclusion, we identify a radio consumption diversity, which occurs in different platforms, locations and times, ranging from an faithful audience to the traditional radio model to an audience that expend it time on a variety of media devices. Aspects such as everyday relationships, routines, memories related to the environment and the diversity of content offer affect the consumption patterns of the research participants.